Chapter 3 Visible Prowess?: Reading Men's Head and Face Wounds in Early Medieval Europe to 1000 CE - DeVries, Kelly (Explorations in Medieval Culture, 2015)
The spectacle of the wounded body figured prominently in the Middle Ages, from images of Christ's wounds on the cross, to the ripped and torn bodies of tortured saints who miraculously heal through divine intervention, to graphic accounts of battlefield and tournament wounds-evidence of which survives in the archaeological record-and literary episodes of fatal (or not so fatal) wounds. This volume offers a comprehensive look at the complexity of wounding and wound repair in medieval literature and culture, bringing together essays from a wide range of sources and disciplines including arms and armaments, military history, medical history, literature, art history, hagiography, and archaeology across medieval and early modern Europe. Contributors are Stephen Atkinson, Debby Banham, Albrecht Classen, Joshua Easterling, Charlene M. Eska, Carmel Ferragud, M.R. Geldof, Elina Gertsman, Barbara A. Goodman, Máire Johnson, Rachel E. Kellett, Ilana Krug, Virginia Langum, Michael Livingston, Iain A. MacInnes, Timothy May, Vibeke Olson, Salvador Ryan, William Sayers, Patricia Skinner, Alicia Spencer-Hall, Wendy J. Turner, Christine Voth, and Robert C. Woosnam-Savage.